BASIS OF FORMATION OF PROFESSIONAL COMMUNICATIVE COMPETENCE IN FUTURE TRANSLATION AVIATION INDUSTRY - Білоус, Наталія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article specifies training conditions required for professional communicative competence of future translators in the area of aviation. The goal of training is determined and characterized as a condition which is most effective while training future translators as competent professionals and communicative individuals ready to work in the area of aviation